Construction and Simulation of a Planar Transformer Prototype (2021)
This paper illustrates the design and building of a planar transformer prototype with a 1:1 transformation ratio for high-frequency applications in power electronics. By using reference literature and considering the ferrite core dimensions, the windings were conceived and exported to Gerber format using PCB design software. The transformer prototype was then assembled and tested under laboratory conditions for frequencies from 800 Hz to 5 MHz, which showed a sinusoidal wave at the transformer output from 1.3 kHz onwards and a better performance starting at 10 kHz, where the loses were significantly reduced and the transformation ratio was closer to the originally designed. As a final step, a finite element method (FEM) analysis was carried out to understand the electromagnetic flux behavior using a 3D Multiphysics simulation software. The 3d building process and details are explained step by step and the resulting magnetic flux density is graphically shown for the core and the windings.